Revolutionizing Lung Cancer Detection: Unveiling the Power of VGG19 - Prasad , Puvvada Harsha Siva; Daswanth , Nedunuri Madhu Venkata Sai; Sai Pavan Kumar, Chinni Venkata; Yeeramally, Nishanth; Mohan, V. Murali; Satish, T. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Lung cancer is a very common and dangerous type of cancer worldwide. Detecting and figuring out what type of lung cancer someone has early can help them get better treatment and have a higher chance of surviving. In our research, we suggest a way to find and categorize lung cancer using fancy computer methods called deep learning. We use a smart computer program called VGG19, which is good at understanding pictures, to look at special pictures of lungs called CT scans. Then, we use another computer program that’s good at guessing, called a probabilistic neural network, to say if the cancer is not so bad, adenocarcinoma, or squamous cell carcinoma. We test our way against another smart program called VGG16 and prove that our way is better at getting things right. Finding lung cancer is hard because the pictures of lumps in the lungs are all different and sometimes not very clear. However, we predict lung cancer with better accuracy by using a deep-learning model called VGG19. After the training, the model got an accuracy of 97.76.